Effects of grazing prohibition on nirK- and nirS-type denitrifier communities in salt marshes - Li, Niu; Li, Jingrou; Nie, Ming; Wu, Ming; Wu, Jihua (Frontiers in Microbiology, 2023)
Intr oduction: Grazing prohibition is an effective management practice to restore salt marsh functioning. However, the effects of grazing exclusion on denitrifying microbial communities and their controlling factors in salt marshes remain unclear. Methods: In this study, we surveyed soil physicochemical properties and above-and below-ground biomass and using quantitative polymerase chain reaction and Illumina MiSeq high-throughput sequencing technology to determine the relative abundance, composition, and diversity of nitrite reductase nirS-and nirK-type denitrifying bacterial communities associated with grazing prohibition treatments and elevations. Results: The abundance of nirS-type denitrifiers increased with grazing prohibition time, whereas the abundance of nirK-type denitrifiers remained unaltered. Moreover, nirS-type denitrifiers were more abundant and diverse than nirK-type denitrifiers in all treatments. Grazing prohibition significantly altered the operational taxonomic unit richness, abundance-based coverage estimator, and Chao1 indices of the nirS-type denitrifying bacterial communities, whereas it only minimally affected the structure of the nirK-type denitrifying bacterial community. Discussion: The results imply that the nirS community, rather than nirK, should be the first candidate for use as an indicator in the process of salt marsh restoration after grazing prohibition. Substances of concern, total nitrogen, and salinity were the key environmental factors affecting the abundance and community composition of nirS and nirK denitrifiers. The findings of this study provide novel insights into the influence of the length of grazing prohibition and elevation on nirS-and nirK-type denitrifying bacterial community composition in salt marshes.